PENGARUH FREKUENSI PENGGUNAAN TEH DAUN TEMPUYUNG KERING (Sonchus arvensis) TERHADAP DAYA LARUT KALSIUM OKSALAT - Ana Hidayati M; Yusrin Herlisa Anggraini (JURNAL KESEHATAN, 2009)
Abstract Background: Tempuyung (Sonchus arvensis) is one of the potent medicinal plants as breaking Facilitate Kidney stones and urine. Potassium in lempuyung will remove calcium and oxalate join that can form kidney stones, which can dissolve and come out with urine. The use of tea leaves tempuyung (Sonchus arvensis) with boiled or soaked in boiling water for current time. Use tempuyung tea once or twice a day for 30 Consecutive days, it is necessary to do research on the influence of frequency of use of dried tea leaves tempuyung (Sonchus arvensis) on solubility of calcium oxalate (CqC2Oq. This study aims to find out the Concentration of dry tea leaves tempuyung (Sonchus arvensis) and the weight of calcium oxalate (C2Oa Co) that have the optimum calcium oxalate solubility maximum, determine the solubility of calcium oxalate by frequency of use of dried tea leaves lx daily tempuyung ond 2x a day, and luow inlluence the frequency of use of dried tea leys’ to tempuyung solubility of calcium oxalate. The method used in tempuyung leaves once a dry and 2 times a dry for seven consecutive days Population Research: tempuyung tea legates, bound variable is the frequenq of use qnd vqriable elimination tempuyung is the power to dissolve the tea tempuyung calcium oxalate (Ca C2OQ. The method used in tempuyung lefts once a day and 2 times a day for seven consecutive days with repeat 5 times. The results: The results showed that the frequency of use of tea leaves tempuyung with 2x daily dose had calcium oxalate solubility is greater than the frequency of use of tea leaves tempuyung with lx daily dose is after 2 x daily for 7 consecutive days has solubility of calcium Oxalic of 27.49%. The longer the time the use of the tea leaves tempuyung solubility of calcium oxalate is also growing, and there is the influence of Frequency of use of the tea leaves to tempuyung solubility of calcium oxalate. Keywords: frequency of use empuyung tea, dried tempuyung (Sonchus arveruis), and the solubility of calcium oxalate (CaC2O4.